Bloodtide - Burgess, Melvin (Andersen London, 1999)
London is in ruins, in the hands of two warring families of ganglords, the Volsons and the Conors. To cement a truce between the two families, Val Volson offers Conor the hand of his 14 year old daughter, Signy. The wedding feast is disrupted by the dramatic coming to life of a mysterious one-eyed prisoner. The people are in no doubt that it is the god Odin, come to play a part in the affairs of men. Suggested level: secondary